PEMBERDAYAAN GURU MENYUSUN E-BAHAN AJAR BERBASIS POTENSI LOKAL BANGKA BELITUNG BERMUATAN PENDIDIKAN KONSERVASI - Fitri Wardani, Erika; Yuanita (Unmuh Babel Press, 2021)
Bangka Belitung as one of the provinces that produces tin has had a positive impact, one of which is increasing the regional economy, but it also has a negative impact, namely causing environmental damage. Therefore it is important to provide education through regional potential so that the existing environment is maintained and preserved which of course requires cooperation involving all elements of society. Educational institutions play an important role in producing future generations who care about the environment and teachers as agents of change for their students must be able to become facilitators in the learning process so that learning can run optimally. Efforts that can be made is to facilitate students by providing teaching materials. In the current industrial era 4.0, the learning process should be able to adapt to technological developments where learning materials or materials must be accessible to students anywhere and anytime in all situations. Another problem that reinforces the importance of carrying out this activity is that the teachers at MA Sabilul Muhtadin have never produced teaching materials both printed and electronic. The method used in this activity is the lecture method by delivering material, question and answer, and practice. This activity aims to encourage teachers to produce teaching materials in electronic form based on local potential containing conservation education.